Alpha 2 Delta (α2δ) Ligands, Gabapentin and Pregabalin: What is the Evidence for Potential Use of These Ligands in Irritable Bowel Syndrome - Gale, Jeremy; Houghton, Lesley A. (Frontiers in Pharmacology, 2011)
Irritable bowel syndrome (IBS) is a complex disorder that is characterized by abdominal pain and altered bowel habit, and often associates with other gastrointestinal symptoms such as feelings of incomplete bowel movement and abdominal bloating, and extra-intestinal symptoms such as headache, dyspareunia, heartburn, muscle pain and back pain. It also frequently coexists with conditions that may also involve central sensitization processes, such as fibromyalgia, irritable bladder disorder and chronic cough. This review examines the evidence to date on gabapentin and pregabalin which may supports further and continued research and development of the α2δ ligands in disorders characterized by visceral hypersensitivity, such as IBS. The distribution of the α2δ sub-unit of the voltage-gated calcium channel, possible mechanisms of action, pre-clinical data which supports an effect on motor-sensory mechanisms and clinical evidence that points to potential benefits in these patients with IBS will be discussed.